Influence of Social Media on Self-Identity Formation and the Development of Interpersonal Ability in University Students - Muhammad Farih Ramdlani; Hani Atul Khoiriyah; Uthman Shehu Lawal (Al-Qalam Institue, 2025)
This study aims to explore the influence of social media on the formation of students' self-identity and interpersonal skills. In a social context, social media offers opportunities for students to express themselves and network, but it also brings challenges such as social pressure and a decline in face-to-face interaction. This study was conducted with a descriptive qualitative approach in State Islamic universities, using interview, observation, and documentation techniques to collect data. The results show that social media allows students to form digital identities through tailored content, but it often raises unrealistic social expectations. In addition, reliance on social media reduces the intensity and quality of face-to-face interactions, which impacts interpersonal skills such as empathy and listening. This research makes an important contribution to understanding the dynamics of social media in the socio-cultural context of Indonesia, but it has limitations in population coverage. These findings are expected to serve as a basis for further research and the development of more thoughtful social media use strategies.